Targeted bacteriophage application to control water contamination by Escherichia coli, Vibrio and Salmonella - Raiana, Anika; Khair, Salwa; Shaik, Lamisa; Shetu, Sadia Zaman (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Biotechnology 2022.